Schriften zur Dialektik und Rhetorik = Principal writings on dialectic and rhetoric : principal writings on rhetoric - Melanchthon, Philip, 1497-1560; Strohm, Stefan; Weaver, William P.; Wels, Volkhard (Berlin ; Boston : De Gruyter, 2017)
The need for a new critical edition of Philip Melanchthon's philosophical works is particularly clear in the case of his writings on rhetoric. That Melanchthon played a central role in the transformation of the ancient discipline has been well established by historians. His writings on rhetoric have proven significant sources for several academic fields, including church history, Scriptural interpretation, the history of science, and the reception of classical literature. Remarkably, two of the three principal writings have not been published in their entirety since the sixteenth century. This volume collects critical editions of the three principal writings to provide a more complete record of Melanchthon's teaching of rhetoric. It includes critical editions of De Rhetorica (1519), Institutiones Rhetoricae (1521), and Elementa Rhetorices (1531). In addition to the three principal writings, this volume collects a new edition, based on a 1911 edition by Hanns Zwicker, of Dispositiones Rhetoricae (c. 1553), a manuscript compilation of 161 model themes. Scholars will find in this volume the major sources for Melanchthon's theory and practice of rhetorical instruction.
Frontmatter -- Inhaltsverzeichnis / Table of Contents -- Zur Edition der "Melanchthonis opera philosophica" -- Volume Introduction / Weaver, William P. -- De Rhetorica Libri Tres -- Editorischer Bericht / Strohm, Stefan / Schmid, Hartmut -- Edition / Strohm, Stefan / Schmid, Hartmut -- Anhang / Strohm, Stefan / Schmid, Hartmut -- Institutiones Rhetoricae -- Editorial Report / Weaver, William P. -- Institutiones Rhetoricae Philippi Melanchthonis / Weaver, William P. -- Elementa Rhetorices -- Editorischer Bericht / Wels, Volkhard -- Elementorum Rhetorices Libri Duo / Wels, Volkhard -- Dispositiones Aliquot Rhetoricae -- Editorial Report / Weaver, William P. / Zwicker, Hanns -- Melanchthons Dispositiones rhetoricae vom Jahre 1553 / Weaver, William P. / Zwicker, Hanns -- Dispositiones aliquot rhetoricae dictatae a Domino Philippo Melanthone Vitebergae / Weaver, William P. / Zwicker, Hanns -- Indexes -- Index of Bible Citations -- Index of Citations -- Index of Names -- Index of Terms.
In Latin.
Online resource; title from PDF title page (publisher's Web site, viewed 08. Jan 2018).
eBooks on EBSCOhost
Keywords: Rhetoric -- Early works to 1800.; Rhétorique -- Ouvrages avant 1800.; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES / Rhetoric; REFERENCE / Writing Skills; Rhetoric; Early works